The shadow throne - Nielsen, Jennifer A. (New York : Scholastic Press, 2014)
Young King Jaron has had nothing but trouble with his advisors and regents since he ascended the throne of Carthya, and now King Vargan of Avenia has invaded the land and captured Imogen--and Jaron must find some way to rescue her and save his kingdom.
Booklist, January 2014
Kirkus Review, January 2014
5.1
5-8
Keywords: Kings and rulers -- Juvenile fiction; Rescues -- Juvenile fiction; Battles -- Juvenile fiction; Kings, queens, rulers, etc. -- Fiction; Rescues -- Fiction; Battles -- Fiction; Adventure and adventurers -- Fiction; Kings and rulers -- Fiction; Rescue work -- Fiction; Battles -- Fiction; Adventure fiction; Adventure fiction